2009
DOI: 10.1007/s10295-009-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

High cell density fermentation of Gluconobacter oxydans DSM 2003 for glycolic acid production

Abstract: Gluconobacter oxydans has a lower biomass yield. Uniform design (UD) was applied to determine the optimum composition of the critical media and their mutual interactions for increased biomass yield of Gluconobacter oxydans DSM 2003 in shake flasks. Fed-batch fermentation process for biomass was optimized in a 3.7-l fermentor. By undertaking a preliminary and improved fed-batch fermentation-process strategy, a cell density of 6.0 g/l (DCW) was achieved in 22 h and 14.1 g/l (DCW) in 35 h, which is the highest ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 14 publications
2
27
1
Order By: Relevance
“…Importantly, in addition to relatively low price of glucose, our experiment results showed that similar final cell concentrations were achieved for both the GDHE50 strain on 10 g/l of glucose and the wild-type strain 621H on 73 g/l of sorbitol, while the latter high concentration of sorbitol was reported to be the optimal sorbitol concentration for G. oxydans DSM 2003 to gain high-density fermentation [5]. It might therefore suggest that the operating cost of biotransformation systems using the engineered G. oxydans in this study could be potentially reduced.…”
Section: Oxidation Of Ethylene Glycol To Glycolic Acidsupporting
confidence: 60%
See 1 more Smart Citation
“…Importantly, in addition to relatively low price of glucose, our experiment results showed that similar final cell concentrations were achieved for both the GDHE50 strain on 10 g/l of glucose and the wild-type strain 621H on 73 g/l of sorbitol, while the latter high concentration of sorbitol was reported to be the optimal sorbitol concentration for G. oxydans DSM 2003 to gain high-density fermentation [5]. It might therefore suggest that the operating cost of biotransformation systems using the engineered G. oxydans in this study could be potentially reduced.…”
Section: Oxidation Of Ethylene Glycol To Glycolic Acidsupporting
confidence: 60%
“…Several studies were carried out to optimize culture conditions of G. oxydsans on sorbitol or mannose which will not be directly converted into acids in the medium [5]. Due to relatively high cost in using above carbon sources, researchers have been trying to modify mGDH in G. oxydans.…”
Section: Introductionmentioning
confidence: 99%
“…Gluconobacter oxydan is one of the most widely used industrial bacterium for the incomplete oxidization of a wide range of sugars, alcohols and polyols into their respective products . The complete genome sequence of G. oxydans was reported in 2005 .…”
Section: Introductionmentioning
confidence: 99%
“…The partially oxidized products (aldehyde, ketone, and organic acid) are rapidly excreted into the medium. This property makes G. oxydans an important biocatalyst for industrial use [26-28]. In a previous study, many substrates including glycerol, meso-erythritol, 1,3-butanediol, and 2,3-butanediol could be oxidized by the membrane-bound polyol dehydrogenase (GOX 0854 and GOX 0855) in G. oxydans 621H [29].…”
Section: Resultsmentioning
confidence: 99%